Gut barrier impairment by high‐fat diet in mice depends on housing conditions. Issue 4 (21st January 2016) - Müller, Veronika Maria; Zietek, Tamara; Rohm, Florian; Fiamoncini, Jarlei; Lagkouvardos, Ilias; Haller, Dirk; Clavel, Thomas; Daniel, Hannelore
Abstract : Alterations of gut barrier function are associated with changes in intestinal microbial colonization and levels of secondary bile acids, increased portal LPS concentrations and elevated fat tissue inflammatory tone in diet‐induced obese mice housed in a conventional facility, but not in diet‐induced obese mice housed in a specific pathogen‐free facility. Thus, the present study demonstrates that alterations of dominant gut bacterial communities and intestinal barrier integrity in mice fed a high‐fat diet depend on housing conditions. Abstract : Scope: Diet‐induced obesity (DIO) is proposed to cause impairments in intestinal barrier integrity, but contradictory results have been published and it appears that the outcomes depend on other environmental factors. We therefore assessed whether the hygienic status of animal facilities alters the gut barrier in DIO mice. Methods and results: Male C57BL/6N mice were housed in a conventional (CV) or a specific pathogen‐free (SPF) animal facility and were fed identical diets represented by a high‐fat (60kJ% fat) or control diet (11kJ% fat) for 12 wks. Intestinal barrier function in small and large intestine was evaluated in Ussing chambers by electrical resistance and permeability measurements. Jejunal ( p < 0.01) and proximal colonic ( p < 0.05) barrier function was altered in CV DIO mice, but not in SPF DIO mice. Moreover, only CV DIO mice were characterized by metabolic endotoxemia and low‐grade inflammation. High‐throughput 16S rRNA gene sequencing revealed significant differences in fecal bacterial diversity and composition between the two animal facilities, but only in mice fed the HFD. Moreover, cecal DCA concentrations correlated positively with two yet uncultivated Clostridiales species. Conclusions: We demonstrated that housing conditions and associated changes in gut bacterial colonization are pivotal for maintenance of gut barrier integrity in DIO mice.